2006
DOI: 10.1364/oe.14.003467
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon bioimaging with picosecond optical pulses from a semiconductor laser

Abstract: Toward a practical light source for two-photon bioimaging, we have generated kilowatt peak power of 0.77 mum wavelength and 5 ps optical pulse via second-harmonic generation of the amplified output from a gain-switched 1.55 mum semiconductor laser. This compact scheme and stable optical-pulse-source has been successfully used for the two-photon fluorescence bioimaging of actin filaments in PtK2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Here, the peak-power of the laser is represented as average peak pulse repi P P f τ = , then Na is rewritten as peak average Na P P ∝ This relationship, in which Na is proportional to the product of peak P and average P , can be expected to hold true for both picosecond and femtosecond pulse light sources, as long as the peak power and average power are held constant. Our results demonstrate the utility of a picosecond pulse light source with high peak-power and high average power with low repetition rate for two-photon microscopy [11,13,18]. Actually, Konig's group previously reported that two-photon microscopy using a picosecond laser light source is much less harmful to living cells than a femtosecond laser [19].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Here, the peak-power of the laser is represented as average peak pulse repi P P f τ = , then Na is rewritten as peak average Na P P ∝ This relationship, in which Na is proportional to the product of peak P and average P , can be expected to hold true for both picosecond and femtosecond pulse light sources, as long as the peak power and average power are held constant. Our results demonstrate the utility of a picosecond pulse light source with high peak-power and high average power with low repetition rate for two-photon microscopy [11,13,18]. Actually, Konig's group previously reported that two-photon microscopy using a picosecond laser light source is much less harmful to living cells than a femtosecond laser [19].…”
Section: Resultssupporting
confidence: 58%
“…A picosecond pulse laser with a high repetition rate has been used to successfully excite fluorescent materials and achieve biological imaging [17]. In addition, a highly amplified picosecond pulse enabled us to visualize biological specimens and hippocampal neurons in the mouse brain in vivo [11,13,18]. Here, the number of photons absorbed per fluorophore per second Na [16] increases with the pulse width τ, the square of the peak power, and the repetition frequency as follows: 2 peak pulse repi Na P f τ ∝ Therefore, even with long pulse widths (up to a few picoseconds), we can improve the twophoton fluorescence intensity by decreasing the pulse repetition rate and amplifying the picosecond pulse by using a PCF to 6.7 kW under the objective lens.…”
Section: Resultsmentioning
confidence: 99%
“…In order to quantify the suitability of the developed system, the two-photon induced time-averaged fluorescent intensity represents a suitable figure-of-merit (FOM) and can be estimated from P peak × P avg . The calculation arises from nonlinear excitation experiments as the detected signal level from a two-photon process is proportional to this FOM [73]. Semiconductor laser diode systems with amplification schemes have been already successfully demonstrated as light sources for nonlinear microscopy applications [67,74,75].…”
Section: Ec-mlqdl With Postamplification By Tapered Qd-soamentioning
confidence: 99%
“…Another trend towards practical TPM system is the development of compact and turn-key light sources. The emerging compact laser systems are based on semiconductor laser-diode (LD) systems [15,27,[51][52][53]59,60] , optical fiber laser systems [57,58,61] , and even chip-size devices [62] . LD has been used as a reliable, low-cost, highperformance light source in scientific research, optical communication, andinformation technologies.…”
Section: Laser Systemmentioning
confidence: 99%